Enhancing the “Digital Literacy” of Professional Teachers in Higher Vocational Education in the New Era: Value, Challenges, and Strategies - Rui, Jiang (Journal of Research in Vocational Education, 2025)
With the in-depth development of the digital economy, digital transformation has become a core driver for the reform of higher vocational education. Professional teachers are the key guarantee of vocational education quality, and their level of digital literacy directly affects the effectiveness of cultivating technical and skilled talents. This paper systematically explores the multidimensional value of enhancing the digital literacy of higher vocational teachers in the new era, and deeply analyzes the current practical challenges, including insufficient awareness and intrinsic motivation among some teachers, lack of target and practicality in training systems, inadequate systematic support for digital teaching resources, and imperfect incentive and evaluation mechanisms. In response to these challenges, this paper proposes an operational system of strategies: strengthening intrinsic motivation by fostering a digital culture and clarifying personal development paths; constructing a systematic, layered, and classified training system integrating theory and practice; promoting the construction of co-built, shared, integrated, and convenient digital teaching resource platforms; and improving development-oriented incentive and evaluation mechanisms. This research aims to provide theoretical reference and practical pathways for higher vocational institutions to promote the enhancement of teachers’ digital literacy, thereby empowering the high-quality development of vocational education to better adapt to industrial upgrading and era changes.